Investigate the extrinsic and intrinsic motivational factors of knowledge transfer in the hospitals - Al-Dalaien A.A.A.-H.; Drus S.M.; Kasim H.; Al-Oqaily A.T. (Science Publications, 2023)
The value of services in knowledge-intensive organizations like the hospitals is created by the tacit knowledge of the health staff. The weak knowledge transfer activities among the health staff effects on the performance level of the health care services. Hospitals are dependent on continuously learning from mistakes and to make improvements and then to transfer this newly acquired knowledge between units and workers in the organization. It is important to enhance the knowledge transfer behaviors of knowledge source and recipients in the hospitals. This study aims to investigate the extrinsic and intrinsic motivational factors that would be adopted to improve the knowledge transfer processes among the health staff. The data of this study were collected from 475 doctor and nurses that work in three Jordanian hospitals; Albashir Hospital, Jordan University Hospital and Al-Issra Hospital. The collected data were analyzed using many tests such as validity, reliability, demographic and descriptive analysis. The significant results show that there are many extrinsic motivational factors would be adopted to improve the knowledge transfer by the knowledge source and recipients such as reward, ideal salaries, promotions, satisfaction of work position, stability of labor and reputation feedback. On the other hand, there are many intrinsic motivational factors that would be applied to enhance the knowledge transfer such as arduous relationship, altruism, shared understanding, champions and enjoyment to help others. This study helps the hospitals to identify the motivational factors that would be adopted to improve the knowledge transfer processes in order to enhance the quality of health care services. 2020 Ahmad Aabed Al-Hayy Al-Dalaien, Sulfeeza Mohd Drus, Hairoladenan Kasim and Ali Taha Al-Oqaily.